2019
DOI: 10.1155/2019/7917894
|View full text |Cite
|
Sign up to set email alerts
|

Antihepatitis B Surface Antigen and Hepatitis C Antibodies among Pregnant Women in an Urban Area of Mwanza City, Tanzania

Abstract: Background. Hepatitis B and hepatitis C viruses (HBV and HCV) are life-threatening infections of public health importance due to their association with cirrhosis and hepatocellular carcinoma. Despite HBV being moderately endemic in many low-income countries, there is no routine HBV vaccination among child bearing aged women making them at risk of transmitting infections to the foetus during pregnancy. This study investigated the seroprevalence of antihepatitis B surface antibodies (anti-HBs) and HCV antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
4
1
3
Order By: Relevance
“…This finding is comparable to a study conducted in southern Ethiopia (1.8%) [ 43 ]. However, our result is higher than studies done in Tanzania (0.3%) [ 44 ] and Bahir Dar (0.6%) [ 20 ]. In contrast, our finding is lower than studies done in East Wollega (8.1%) and Egypt (6.1%) [ 18 , 45 ].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…This finding is comparable to a study conducted in southern Ethiopia (1.8%) [ 43 ]. However, our result is higher than studies done in Tanzania (0.3%) [ 44 ] and Bahir Dar (0.6%) [ 20 ]. In contrast, our finding is lower than studies done in East Wollega (8.1%) and Egypt (6.1%) [ 18 , 45 ].…”
Section: Discussioncontrasting
confidence: 92%
“…In high endemic areas, coinfection of HBV and HCV is more dangerous in pregnant women and their infants than monoinfection [ 29 , 36 , 43 ]. In contrast to this finding, no coinfection of these viruses was detected in studies conducted in Ethiopia and elsewhere [ 20 , 44 ]. The differences might be due to differences in sample sizes, awareness of transmission methods, risk factors, and diagnostic kit employed.…”
Section: Discussioncontrasting
confidence: 72%
“…Previous studies from the west and northwest of Iran revealed almost no risk factor for HCV seropositivity among pregnant women [ 21 , 22 ]. The same findings have been reported in the study of Chibwe et al [ 25 ]. In contrast, some studies from Egypt, Pakistan, and Ghana have reported a significant association between the history of blood transfusion and HCV seropositivity [ 30 , 35 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Studies have documented that there was co-infection of HBV and HCV among pregnant women, similar to our ndings [37,44]. In contrast to this nding, no co-infection of these viruses was detected in studies conducted in Ethiopia and elsewhere [17,29,45].…”
Section: Discussionsupporting
confidence: 87%
“…This nding is comparable to a study conducted in southern Ethiopia 1.8% [44]. However, our result is higher than Tazania 0.3% [45] and Bahir Dar 0.6% [17]. In contrast, our nding is lower than studies done in East Wolega 8.1% and Egypt 6.1% [29,46].…”
Section: Discussionsupporting
confidence: 69%